Analisis Lintas Lapisan Energi Transmisi Pada Domain Radio Frekuensi Terhadap Pengaruh Hujan - Made Sutha Yadnya; I Ketut Perdana Putra (LPPM Universitas Mataram, 2026)
This study analyzes the effect of rainfall on transmission energy in the radio frequency domain in Mataram City, focusing on wireless communication systems operating at 2.4 GHz to 30 GHz and 5G mmWave scenarios. The research employs a link budget-based analytical approach integrating the ITU-R P.838 rain attenuation model and channel performance simulation using RSSI, SINR, and transmission energy parameters. The results indicate that rainfall in the study area is predominantly light with stratiform characteristics; however, it still contributes to a measurable degradation in signal quality. Increasing rainfall intensity leads to a reduction in RSSI and SINR values and decreases transmission energy efficiency. The impact becomes more significant at higher frequencies, where 2.4 GHz systems remain relatively stable, while frequencies above 10 GHz exhibit notable performance degradation, and mmWave systems show the highest risk of outage. These findings confirm that tropical rainfall conditions directly affect radio frequency communication performance. Therefore, adaptive system design and mitigation strategies are required to maintain network reliability, particularly for 5G implementations